2020
DOI: 10.3390/app10238356
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Nanocrystals: Production, Physicochemical Assessment, and In Vitro Evaluation of the Antimicrobial Effects against Bacterial Loading of the Implant Fixture

Abstract: Background: This study aimed to prepare and study physicochemical properties as well as the antibacterial action of curcumin nanocrystals inside the implant fixture against Escherichia coli (E. coli), Staphylococcus aureus (S. aureus), and Enterococcus faecalis (E. faecalis). Methods: Curcumin nanocrystals were prepared via precipitation combined with the spray drying method. The produced curcumin nanocrystals were characterized by dynamic light scattering (DLS), scanning electron microscopy (SEM), powder X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Nanomaterials apply their antibacterial actions on bacteria by several mechanisms [ 46 , 47 ]. Based on the reports, the physicochemical possessions of nanoparticles are actually vital in their antimicrobial properties [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials apply their antibacterial actions on bacteria by several mechanisms [ 46 , 47 ]. Based on the reports, the physicochemical possessions of nanoparticles are actually vital in their antimicrobial properties [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The interaction between the membrane and nanomaterials also leads to local pores in the membrane and harms the bacteria due to the passing of nanoparticles into the bacteria and the interaction of bacteria‘s proteins with DNA [ 52 ]. Some nanomaterials are also able to mix with the bacterial cell wall to release their antimicrobial material into the cytoplasm [ 46 , 53 ]. Antimicrobial nanofibers can also pass through the bacteria pores due to their very small diameter and can then disrupt the bacteria’s different functions [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nanocrystals designed for curcumin delivery that ranged in size from 2 to 40 nm resulted in curcumin having better water diffusion. Due to the high bioavailability of the curcumin-loaded nanocrystals, which can be attributed to their reduced particle size, significant antimicrobial activity was observed [129]. Another study revealed that curcumin-loaded nanocrystals improved curcumin cellular uptake and bioavailability against Escherichia coli, Streptococcus aureus, and Micrococcus luteus, displaying their antimicrobial potential [130].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The final stage of biofilm development is a dissociation of bacterial cells from the biofilm structure, followed by bacterial dispersion to the adjacent locations [ 19 ]. The high ability of staphylococci to form a biofilm and to resist antibiotic activity is the reason of ongoing search for new counter-measures, including application of nano-silver [ 20 ] or plant-based products [ 21 ], to name just a few of them. Nevertheless, until the new approaches are introduced, the routine therapy of bone infections involves invasive surgical procedures and prolonged antibiotic therapy.…”
Section: Introductionmentioning
confidence: 99%